2021
DOI: 10.1007/s40789-020-00385-2
|View full text |Cite
|
Sign up to set email alerts
|

Water-retaining properties of NCZ composite dust suppressant and its wetting ability to hydrophobic coal dust

Abstract: Coal dust is a primary threat to underground coal miners. The most common approach to control coal dust is hydraulic methods, such as water spray and coal seam water injection. To improve the dust suppressant efficiency of hydraulic methods, a novel chemical composite dust suppressant, called NCZ, was prepared in this study using calcium chloride (CaCl2), magnesium chloride (MgCl2), and nonionic surfactants using a thermal synthesis method. The water-retaining properties of NCZ powder and its solutions were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Note that the cumulative number of PM10 particles is the total number of particles with sizes of 0.3, 0.5, 1.0, 2.0, 5.0, and 10.0 µm. It can be computed using Equation (7). c = ∑ pm= pm 0.3 + pm 0.5 + pm 1.0 + pm 2.0 + pm 5.0 + pm 10.0 (7) where c is the cumulative number of PM10 particles; and pm i is the number of particles with a particle size of i (i = 0.3, 0.5, 1.0, 2.0, 5.0, 10.0).…”
Section: ) Wind Erosion Massmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the cumulative number of PM10 particles is the total number of particles with sizes of 0.3, 0.5, 1.0, 2.0, 5.0, and 10.0 µm. It can be computed using Equation (7). c = ∑ pm= pm 0.3 + pm 0.5 + pm 1.0 + pm 2.0 + pm 5.0 + pm 10.0 (7) where c is the cumulative number of PM10 particles; and pm i is the number of particles with a particle size of i (i = 0.3, 0.5, 1.0, 2.0, 5.0, 10.0).…”
Section: ) Wind Erosion Massmentioning
confidence: 99%
“…It can be computed using Equation (7). c = ∑ pm= pm 0.3 + pm 0.5 + pm 1.0 + pm 2.0 + pm 5.0 + pm 10.0 (7) where c is the cumulative number of PM10 particles; and pm i is the number of particles with a particle size of i (i = 0.3, 0.5, 1.0, 2.0, 5.0, 10.0).…”
Section: ) Wind Erosion Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan et al, 2018;Wu et al, 2019). For this reason, dust monitoring control during the handling of different mining technologies requires extensive investigation, including information on the physicochemical characteristics of the deeply inhalable (particle size below 10 µm) and respirable fractions (particle size below 4 µm and 2.5 µm), both of which could be a key factor in the prevention of coal dust problems in mining, such as diverse authors are contributing (Zhang et al 2020;Szkudlarek and Janas 2021;Jiang and Luo 2021;Liu et al 2021;Reed et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the physical and chemical properties of dust in mines, the wettability of copper mine blasting dust is mainly controlled by particle size and pore structure (Jin et al 2021). A molecular dynamics simulation study indicated that larger coal dust particle has higher wettability (Zhang et al 2021).…”
mentioning
confidence: 99%